Gay representation, queer resistence, and the small screen : a reception study of gay representations among Flemish fans of contemporary television fiction - Dhaenens Frederik (Gent : Academia Press, 2011)
Fonds Suzan Daniel (FSD)
Working Papers Film & TV Studies 2011/1
Engels
Monografie